Physical activity promotion intervention improved physical activity knowledge, confidence and behaviour among diverse immigrant women: pre–post multiple methods feasibility study - Anna R Gagliardi; Nazilla Khanlou; Jenna Smith-Turchyn; Catherine M Sabiston; C M Friedenreich; Jennifer R Tomasone; Sharon Iziduh; Jocelyn Lee; Bora Umutoni; Priya Brahmbhatt (BMJ Open)
Objectives Little prior research investigated how to promote physical activity (PA), which can reduce cancer risk, to immigrant women. The overall aim of the current study was to pilot test education session feasibility. The objectives were to assess participation in, satisfaction with and potential impact of the education session, knowledge needed to refine the education session prior to a future trial.Design Pre–post multiple-methods comparative cohort,Setting Canadian immigrant settlement agencies recruited intervention and control women.Participants Intervention: 60 baseline, 53 education (49 virtual group, 4 video only), 1 month (43 virtual, 4 video), 6 months (38 virtual, 4 video), 37% African black; control: 41, 32% African black.Results Among intervention women, PA knowledge increased significantly from baseline at 1 (p<0.001) and 6 (p=0.01) months, as did PA confidence at both time points (p<0.001). PA behaviour increased significantly from baseline at 1 and 6 months for (p<0.001), moderate (p=0.02) and mild (p=0.05) intensity PA. Total PA metabolic equivalent units (METs) also increased significantly from baseline at both time points (p=0.01). PA confidence (p=0.002) and behaviour assessed by weekly minutes of vigorous (p=0.04, n2=0.05) and moderate (p=0.005) intensity PA, and total PA METs (p=0.01) were significantly greater among intervention women compared with control women. PA knowledge was greater among intervention women compared with control women but not significantly (p=0.8).Conclusions The findings underscore an important health promotion role for community agencies, which may interest policy-makers, healthcare leaders and health promotion specialists.